Process-dependent structural and deformation properties of extrusion blow molding parts. (August 2019) - Dorp, Esther Ramakers-van; Blume, Christian; Haedecke, Tobias; Pata, Vladimir; Reith, Dirk; Bruch, Olaf; Möginger, Bernhard; Hausnerova, Berenika
Abstract: Extrusion blow molding (EBM) is a manufacturing technique to produce plastic hollow containers. Requirements on complex geometries are steadily increasing, especially in packaging and automotive, although some issues of EBM remain unclear. Consequently, EBM parts are still over-dimensioned. Thus, processing-structure-properties relationship is investigated via dynamic mechanical analysis and differential scanning calorimetry. Storage modulus and crystallinity data were obtained at various flow directions, draw ratios and mold temperatures. The data evaluation of the influence of these three parameters on the storage modulus proved as statistically significant, process-dependent, for specific measuring temperature ranges. Relaxation processes during sample storage and elevated measuring temperatures can explain the process independency for the flow direction and the draw ratio for specific measuring temperature ranges from which the mold temperature was unaffected. Mold temperature and draw ratio had a significant influence on crystallinity of EBM containers; higher mold temperature and draw ratio caused higher crystallinities due to the flow-induced orientation. Graphical abstract: Image 1 Highlights: Processing-structure-properties relationship in extrusion blow molded investigated. Flow direction, draw ratio and mold temperature were found process-dependent. Mold temperature and draw ratio influenced crystallinity of parts. Storage and testing temperatures affected significance of dependencies.